REVOLUTIONIZING RURAL HEALTHCARE: THE IMPACT OF TELEPHARMACY ON UNDERSERVED POPULATIONS - Faisal Fahd Awad Alenazi, Nouf Muhaimid Al-Mutairi,Ali Dhifallah Bakheet Alzahrani,Mohammed Dughayyim Shaman Alharbi‏,Talal Mohammd Alotaibi,Asaad Hamdan Alruwaili,Mohammed Badah Albidah,Fares Saleh A Aljadiai,; Sami Abdullah Alwagdani,Turki Hasen Mohsen Alhakami,Ayed Turky H Alotybie,Dhaifallah Meqad Albqomi,Saeed Murdhi Saeed Aldawsari,Mohammad Zaeed Alqahtani,Abdullah Yahya Aqili (Chelonian Research Foundation, 2022)
Telepharmacy provides a practical remedy for healthcare disparities in rural regions by providing remote access to pharmacy services. The objective of this study is to investigate the impact of telepharmacy on healthcare services in a rural community, specifically in terms of medication accessibility, convenience, health monitoring, patient satisfaction, trust in healthcare providers, financial savings, and overall well-being. The findings demonstrate that telepharmacy is essential for enhancing patient satisfaction, instilling trust in healthcare practitioners, and reducing healthcare costs in distant regions. Telepharmacy had a positive impact on the quality of life, resulting in an overall improvement in the well-being of those using remote pharmacy services. The study highlights the significant positive impacts of telepharmacy on healthcare services in remote regions. Future study might focus on addressing the concerns raised by participants who have neutral or somewhat negative views in order to enhance the effectiveness and acceptance of telepharmacy services. Continued research and progress in telepharmacy are essential to provide equitable access to high-quality pharmacy services and improved health outcomes for those residing in distant regions. Keywords: Telepharmacy, contentment, medicine availability, healthcare oversight, ease of use, remote area.